Perinatal iron deficiency combined with a high salt diet in adulthood causes sex‐dependent vascular dysfunction in rats. (22nd August 2019) - Woodman, Andrew G.; Noble, Ronan M. N.; Panahi, Sareh; Gragasin, Ferrante S.; Bourque, Stephane L.
Abstract : Key points: Perinatal iron deficiency causes changes in offspring mesenteric artery function in adulthood, particularly in males, which can be exacerbated by chronic intake of a high salt diet. Perinatal iron deficient male offspring exhibit enhanced conversion of big endothelin‐1 to active endothelin‐1, coinciding with decreased nitric oxide levels. Perinatal iron deficient male offspring have reduced nitric oxide‐mediated endothelial‐dependent vasodilatation coincident with increased vascular superoxide levels following consumption of a high salt diet. Perinatal iron deficiency has no apparent effects on vascular function in female offspring, even when fed a high salt diet. These results help us better understand underlying vascular mechanisms contributing to increased cardiovascular risk from perinatal stressors such as iron deficiency. Abstract: Pre‐ and immediate postnatal stressors, such as iron deficiency, can alter developmental trajectories and predispose offspring to long‐term cardiovascular dysfunction. Here, we investigated the impact of perinatal iron deficiency on vascular function in the adult offspring, and whether these long‐term effects were exacerbated by prolonged consumption of a high salt diet in adulthood. Female Sprague Dawley rats were fed either an iron‐restricted or ‐replete diet prior to and throughout pregnancy. Six weeks prior to experimentation at 6 months of age, adult offspring were fed either a normal or high salt diet. Mesenteric artery responses to vasodilators and vasoconstrictors were assessed ex vivo by wire myography. Male perinatal iron deficient offspring exhibited decreased reliance on nitric oxide with methacholine‐induced vasodilatation (interaction P  = 0.03), coincident with increased superoxide levels when fed the high salt diet ( P  = 0.01). Male perinatal iron deficient offspring exhibit enhanced big endothelin‐1 conversion to active endothelin‐1 ( P  = 0.02) concomitant with decreased nitric oxide levels ( P  = 0.005). Female offspring vascular function was unaffected by perinatal iron deficiency, albeit the high salt diet was associated with impaired vasodilation and decreased nitric oxide production ( P  = 0.02), particularly in the perinatal iron deficient offspring. These findings implicate vascular dysfunction in the sex‐specific programming of cardiovascular dysfunction in the offspring by perinatal iron deficiency. Key points: Perinatal iron deficiency causes changes in offspring mesenteric artery function in adulthood, particularly in males, which can be exacerbated by chronic intake of a high salt diet. Perinatal iron deficient male offspring exhibit enhanced conversion of big endothelin‐1 to active endothelin‐1, coinciding with decreased nitric oxide levels. Perinatal iron deficient male offspring have reduced nitric oxide‐mediated endothelial‐dependent vasodilatation coincident with increased vascular superoxide levels following consumption of a high salt diet. Perinatal iron deficiency has no apparent effects on vascular function in female offspring, even when fed a high salt diet. These results help us better understand underlying vascular mechanisms contributing to increased cardiovascular risk from perinatal stressors such as iron deficiency.